On the Parametrization of Nonlinear Impulsive Fractional Integro–Differential System With Non-Separated Integral Coupled Boundary Conditions - Rafeeq, Ava Sh. (Science Journal of University of Zakho, 2020)
We give a new investigation of periodic solutions of nonlinear impulsive fractional integro-differential system with different orders of fractional derivatives with non-separated integral coupled boundary conditions. Uniformly Converging of the sequence of functions according to the main idea of the Numerical-analytic technique, from creating a sequence of functions. An example of impulsive fractional system is also presented to illustrate the theory.
Keywords: Caputo fractional derivative; fractional integro-differential; integral coupled boundary conditions; Periodic solutions; successive approximation method